To See History Doxologically: History and Holiness in John Howard Yoder’s Ecclesiology. By J. Alexander Sider - Henreckson, David P. (The journal of theological studies, 2013)
Relations between Anabaptists and more ‘mainstream’ Catholic and Protestant traditions have not always been open and friendly. In recent decades the work of the late Mennonite theologian John Howard Yoder has done much to bridge this old theological divide. Often mediated to those in the mainstream by Stanley Hauerwas, Yoder’s theology has proved remarkably expansive and even ecumenically resonant in its own right. J. Alexander Sider’s new book To See History Doxologically points the reader back to these ecumenical resources, suggesting that even those who have ignored the so-called Radical Reformation tradition will be challenged and edified by Yoder’s perspective on the meaning of history and the church’s place in the divine narrative of salvation.